DAMPAK IN-STORE ATMOSPHERE TERHADAP MINAT BELI KONSUMEN (Studi pada KFC Kota Ternate) - Nurazdiani Nurazdiani (Jurnal Manajemen Sinergi, 2013)
the aim of research to examine the effect of in-store atmosphere toward consumer purchasing interest (Study of KFC) fast-food in Ternate. Teknique to sample removal which using is convenience sampling, adobt as many as 120 respondents. Resorted Linier regression analysus. Outcome of this research indicate that in-store atmosphere has significant influence toward consumer purchasing interest at KFC (fast-food) in Ternate.